Effects of Municipal Solid Waste Landfill on Agricultural Land (Journal of the Bangladesh Agricultural University, 2025)
The study was under taken to identify the effect of municipal solid waste landfill of Shambhuganj, Mymensingh, on agricultural land. Soil samples were collected from landfill, from the adjacent side of the landfill and from 20m, 40m and 60m away from the landfill. Collected samples were analyzed to determine Soil texture, pH, Electrical conductivity, Organic matter, Total nitrogen, C/N ratio and Exchangeable potassium. The results showed that the texture of the collected soil samples is mainly clay loam and soils were acidic in reaction (average pH is found 4.174). The Electrical conductivity ranged from 2.1 to 6.4 mS/cm. Organic matter, Total nitrogen, C/N ratio ranged from 4.52% to 6.81%, 0.44% to 0.20% and 7.56:1 to 14.4:1 respectively. Exchangeable potassium of the soil ranged from and 1369.87 ppm to 4052.66 ppm. Considering the investigated parameters, the land around the landfill site of Shambhuganj, Mymensingh, is not suitable for crop production. The different soil properties are way above the optimum level except the organic matter, which eventually make the land unsuitable for crop production.J Bangladesh Agril Univ 23(2): 141-147, 2025